Comment to “Breaking Barriers in intercultural philosophy: the power of empathy and interrelationship” - Lucas Nascimento Machado (Trans/Form/Ação)
Commented article: PRAZERES, Amanda Sayonara Fernandes. Breaking barriers in intercultural philosophy: the power of empathy and interrelationship. Trans/form/ação: Revista de Filosofia da Unesp, Marília, v. 47, n. 2, e02400274, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/16100.